Groundwater and soil chemistry changes under phreatophytic tree plantations - Jobbagy Gampel, Esteban Gabriel (2007)
The onset of groundwater consumption by plants can initiate a pathway of chemical inputs from aquifers to ecosystems, typically absent in groundwater recharge areas. We explored this biogeochemical transfer and its influence on soils in phreatophytic eucalypt plantations and native grasslands of the Pampas (Argentina). Groundwater and soil chemical observations at three grassland/plantation pairs were complemented with more detailed analyses along a 400-m-long grassland-plantation transect. Although tree plantations showed a widespread and homogeneous salinization of groundwater and soils at all study sites, chemical contrasts between the plantation edge and core were evident along the study transect. Nonsalty, slightly acidic, bicarbonate-dominated waters in the grassland changed sharply within the plantation, with dissolved chloride, sulfate, calcium, and magnesium peaking at the plantation core (200 m away from the grassland) and dissolved sodium, carbonate, bicarbonate, and pH peaking toward the edge (0–50 m away from the grassland) and declining toward the core. In agreement with these differences, soil alkalinization was the strongest at the plantation edge but absent in the core. Groundwater flow simulations using FLOWNET suggested trajectories of increasing length and depth and older groundwater ages (confirmed by tritium analyses) toward the plantation core, explaining the hydrochemical contrasts within the plantation. Flow simulations and chloride mass balances suggested discharges of 250–500 mm yr−1 to the plantations. In our sites phreatophytic discharge controlled solute transfers from groundwater through (1) altered flow within the aquifer, affecting solute transport to the rooting zone, and (2) water uptake plus solute exclusion, concentrating solutes in the rooting zone. While the first mechanism may be restricted to the core of large phreatophytic areas, the second is likely to occur more generally in phreatophytic ecosystems.